2015
DOI: 10.1007/s11104-015-2518-1
|View full text |Cite
|
Sign up to set email alerts
|

Legumes have a greater effect on rhizosphere properties (pH, organic acids and enzyme activity) but a smaller impact on soil P compared to other cover crops

Abstract: Background and aims Plants affect phosphorus (P) cycling through uptake and the mobilization of P from several soil pools into soil solution. The effects of seven cover crop species -three legumes (variable morphology), three cereals (variable domestication degree), one mustard (non-mycorrhizal) -on P cycling were compared in a greenhouse experiment. Methods Monocultures and legume-cereal mixtures were grown in an artificial plant growth substrate across three P input treatments (low P, manure, mineral fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 42 publications
7
22
0
Order By: Relevance
“…Vicia faba released smaller amounts of protons and carboxylates into rhizosphere than Cicer arietinum , but much greater than Triticum aestivum and Zea mays (Zhou et al, 2009; Li et al, 2010; Rose et al, 2010). In Maltais-Landry’s (2015) study, legumes ( Vicia faba and Pisum sativum ) had higher organic acid concentration and phosphatase activity in the rhizosphere compared with cereals crops ( Secale cereale , Avena sativa , and Triticum aestivum ).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Vicia faba released smaller amounts of protons and carboxylates into rhizosphere than Cicer arietinum , but much greater than Triticum aestivum and Zea mays (Zhou et al, 2009; Li et al, 2010; Rose et al, 2010). In Maltais-Landry’s (2015) study, legumes ( Vicia faba and Pisum sativum ) had higher organic acid concentration and phosphatase activity in the rhizosphere compared with cereals crops ( Secale cereale , Avena sativa , and Triticum aestivum ).…”
Section: Introductionmentioning
confidence: 85%
“…However, the conclusions of all these studies mainly focused on independent changes in either root morphological or physiological parameters, such as shoot biomass or carboxylate exudation (Hoffland et al, 1989a,b; Tadano et al, 1993; Neumann and Römheld, 1999; Nuruzzaman et al, 2005; Li et al, 2010; Rose et al, 2010; Vu et al, 2010; Maltais-Landry, 2015), or some correlation between these parameters (Shen et al, 2003; Watt and Evans, 2003; George et al, 2006; Pearse et al, 2007; Zhang et al, 2009). In this study, the PCA method was used as reported before (Tang et al, 2013b) to calculate the relative contribution of the root morphological or physiological response parameter scores to P acquisition, and then quantitatively evaluate the relationship between root morphological and physiological traits in response to P supply and soil types ( Figures 8 and 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian studies have emphasized conservation agriculture and acid soils with poor P availability (LeMare et al 1987;Calegari et al 2013;Balota et al 2014;Fageria et al 2016;Varela et al 2017), while Scandinavian researchers have concentrated on P leaching (Liu et al 2015;Aronsson et al 2016). In the USA, cover crops of different species have been investigated (Lal et al 1978), including their effects on mycorrhizal fungi (Galvez et al 1995;Zibilske and Makus 2009;Rick et al 2011;Maltais-Landry 2015), whereas in China and India, studies have often focused on microbial inoculants (Devi et al 2013;Cui et al 2015). In some African countries, India, and Mexico, with their prevalent traditional smallholder cropping systems, agroforestry and intercropping have been important topics for research (LeMare et al 1987;Tarawali et al 1999;Dinesh et al 2004;Sileshi et al 2008;Castillo-Caamal and Caamal-Maldonado 2011;Devi et al 2013;Tanwar et al 2014;Parihar et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to monocropping, the available iron concentration in peanut rhizosphere was increased in all intercropped cropping systems (i.e., peanuts with different gramineous species: maize, barley, oats, wheat). According to the findings by Maltais-Landry [35], mustard cultivation leads to a slight decrease in soil pH. This may explain the observed increase in the Fe and Mn content in the broad bean leaves.…”
Section: Microelements and Heavy Metals Content In Broad Bean Plantsmentioning
confidence: 74%